Two Case Reports of Peutz Jegher's Syndrome - Hanif, Abdul; Hasina, Kaniz; Hassan, Md. Kamrul; Talukder, Shah Alam; Islam, Md. Kabirul (Journal of Paediatric Surgeons of Bangladesh, 2014)
We are reporting two cases in a family, Elder sister was 10 year old & younger one was 8 years old. Both of them were presented to us with the features of gastric outlet obstruction. Further examination revealed that there is pigmentation on their mucocutanious junction of lips. Their father also had pigmentation on the muco cutanious junction of lips. DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19471